2009
DOI: 10.17159/2078-516x/2009/v21i1a304
|View full text |Cite
|
Sign up to set email alerts
|

Acute and session RPE responses during resistance training: Bouts to failure at 60% and 90% of 1RM

Abstract: Objective. To compare resistance bouts performed to failure atlow (60% 1RM) and high (90% 1RM) workloads for acute rate of perceived exertion (RPE) (per exercise), session RPE (S-RPE) (30 min post), HR (per exercise) and total work (per session, and per exercise).Background. RPE is a convenient method for quantifying intensityin aerobic exercise. However, RPE has recently been extended to exercise modalities dominated by anaerobic pathways such as resistance training (RT). Method. Subjects (N=12) were assessed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
65
1
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(78 citation statements)
references
References 19 publications
10
65
1
2
Order By: Relevance
“…These findings corroborate other research from Pritchett et al [28], who recorded higher sRPE scores and volume load during moderate-load (60% 1RM) resistance exercise to failure compared to high-load (90% 1RM) training. However, Singh et al [27] reported similar sRPE values between resistance exercise targeting strength (3 sets of 5 repetitions using 90% 1RM) and hypertrophy (3 sets of 10 repetitions using 70% 1RM), despite higher relative volume loads in the hypertrophyfocused exercise.…”
Section: Srpe Methodssupporting
confidence: 92%
“…These findings corroborate other research from Pritchett et al [28], who recorded higher sRPE scores and volume load during moderate-load (60% 1RM) resistance exercise to failure compared to high-load (90% 1RM) training. However, Singh et al [27] reported similar sRPE values between resistance exercise targeting strength (3 sets of 5 repetitions using 90% 1RM) and hypertrophy (3 sets of 10 repetitions using 70% 1RM), despite higher relative volume loads in the hypertrophyfocused exercise.…”
Section: Srpe Methodssupporting
confidence: 92%
“…Thus we can only assume that either; participants did not exercise to MF, or the participants were unclear as to how to report their perception of effort. Increasing ratings of effort, despite conditions being controlled by training to supposed MF, were however given with lower load for lower body exercise 29 , as set volume's increased 30 , with increased volume-load 28 , and with increased work rate 26,27 supporting that participants may have expressed their feelings of increasing discomfort 19,25 . Some studies have attempted to differentiate between effort and discomfort during RT and have found that, though participants appear able to report different values for each, there is a similar pattern for both responses.…”
Section: Introductionmentioning
confidence: 93%
“…19,[23][24][25] Certain manipulations of RT variables appear to have the potential to impact upon RPE in unexpected ways and thus may indicate a conflation of perceived effort and discomfort by participants. [26][27][28][29][30] Indeed, even where studies have attempted to differentiate the two, strong relationships in their responses manifest both during traditional RT and blood flow restriction based RT [31][32][33][34] . This may be potentially be due to these studies in some cases using high effort RT conditions known also to anecdotally produce high levels of discomfort (e.g.…”
Section: Figure 3 Scatter Plot Of Rpe-e and Rpe-d For Combined Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Early research indicated that intensity (as measured by percentage of 1 repetition maximum [1RM]) was a key mediating factor and that SRPE increased with increases in the percentage of 1RM lifted (4,18,27). However, Pritchett et al (22) reported higher SRPE at lower relative resistance (% 1RM) during resistance training to failure, noting that participants performed more total volume of work at lower intensities. This led authors to conclude that total volume lifted was a principle mediating factor.…”
Section: Introductionmentioning
confidence: 99%